2010
DOI: 10.1039/b908400b
|View full text |Cite
|
Sign up to set email alerts
|

Studies of water and ice in hydrophilic and hydrophobic mesoporous silicas: pore characterisation and phase transformations

Abstract: A study has been made as a function of temperature of the phase transformation of water and ice in two samples of mesoporous silica gel with pore diameters of ∼50Å. One sample was modified by coating with a layer of trimethylchlorosilane, giving a predominantly hydrophobic internal surface, whereas the unmodified sample has a hydrophilic interface. The pore structure was characterised by nitrogen gas adsorption and NMR cryoporometry and the melting/freezing behaviour of water and ice in the pores was studied b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
66
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(82 citation statements)
references
References 34 publications
15
66
1
Order By: Relevance
“…Taking into account the previous use of silica gel, Vycor and MCM-41 by our team as confinement matrix [36][37][38][39][40], we decided to elaborate a new mesoporous glass with molar composition close to 100% SiO 2 (molar composition of MCM-41). However, previous study showed that MCM-41 was not bioactive [41].…”
Section: Preparation Of Mesoporous Bioactive Glass Samples (92s6)mentioning
confidence: 99%
“…Taking into account the previous use of silica gel, Vycor and MCM-41 by our team as confinement matrix [36][37][38][39][40], we decided to elaborate a new mesoporous glass with molar composition close to 100% SiO 2 (molar composition of MCM-41). However, previous study showed that MCM-41 was not bioactive [41].…”
Section: Preparation Of Mesoporous Bioactive Glass Samples (92s6)mentioning
confidence: 99%
“…Equation (2) indicates that there is a linear relation between the relaxation time T 2 and the pore diameter D. Thus, it is recognized that to calculate the pore diameters in a porous mediums based on its ρ 2 value. In several researches, ρ 2 values were calculated by comparing the T 2 spectrum curves with POSD results from mercury injection porosimetry technique as presented by Chen et al [33] and nitrogen gas adsorption technique as presented by Jahwar et al [34]. Besides, the ρ 2 values can be calculated by empirical formulas of permeability.…”
Section: Theoretical Background Of Nmri Analysismentioning
confidence: 99%
“…Predicting the thickness of QLL always faces challenges especially when the phase transition from water to ice is beyond the bulk freezing. A pertinent example is the freezing of the water confined in thin pores, which can be influenced by many factors such as the geometry confinement that regulates the crystal anisotropy, the curvature effect that depresses the freezing temperature, and the actions of the pore walls on the pore fluid [1,3,11,[14][15][16][17]. Indeed, in chemical, environmental, and civil engineering, the confined freezing is more frequently quoted because almost all materials (except pure metals and crystals) are, more or less, in porous structures, and the phase transition of the water confined in the pores may occur in certain conditions during freezing [3,18].…”
Section: Introductionmentioning
confidence: 99%